Working Inside for Smoking Elimination (Project W.I.S.E.) study design and rationale to prevent return to smoking after release from a smoke free prison - Mello Jennifer; Lopes Cheryl E; Stein LAR; Martin Rosemarie A; Clarke Jennifer G; Friedmann Peter; Bock Beth (BMC, 2011)
Abstract Background Incarcerated individuals suffer disproportionately from the health effects of tobacco smoking due to the high smoking prevalence in this population. In addition there is an over-representation of ethnic and racial minorities, impoverished individuals, and those with mental health and drug addictions in prisons. Increasingly, prisons across the U.S. are becoming smoke free. However, relapse to smoking is common upon release from prison, approaching 90% within a few weeks. No evidence based treatments currently exist to assist individuals to remain abstinent after a period of prolonged, forced abstinence. Methods/Design This paper describes the design and rationale of a randomized clinical trial to enhance smoking abstinence rates among individuals following release from a tobacco free prison. The intervention is six weekly sessions of motivational interviewing and cognitive behavioral therapy initiated approximately six weeks prior to release from prison. The control group views six time matched videos weekly starting about six weeks prior to release. Assessments take place in-person 3 weeks after release and then for non-smokers every 3 months up to 12 months. Smoking status is confirmed by urine cotinine. Discussion Effective interventions are greatly needed to assist these individuals to remain smoke free and reduce health disparities among this socially and economically challenged group. Trial Registration NCT01122589